Biomimetic survival hydrodynamics and flow sensing - Triantafyllou, Michael S. (2018)
The fluid mechanics employed by aquatic animals in their escape or attack maneuvers, what we call survival hydrodynamics, are fascinating because the recorded performance in animals is truly impressive. Such performance forces us to pose some basic questions on the underlying flow mechanisms that are not yet in use in engineered vehicles. A closely related issue is the ability of animals to sense the flow velocity and pressure field around them in order to detect and discriminate threats in environments where vision or other sensing is of limited or no use. We review work on animal flow sensing and actuation as a source of inspiration and as a way to formulate a number of basic problems and investigate the flow mechanisms that enable animals to perform these remarkable maneuvers. We also describe some intriguing mechanisms of actuation and sensing.